MELIHAT LEMBAGA KEUANGAN ANJAK PIUTANG DIBANDINGKAN PERBANKAN DILIHAT DARI ASPEK HUKUM ? - Rani Eka Diansari; Lulu Amalia Nusron (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2020)
This study aims to determine whether there are differences in banking and factoring institutions viewed from the legal aspect. This study uses secondary data obtained from the results of previous studies. This research belongs to the type of library research (library research), which is looking for data from various kinds of library information including documents, newspapers, magazines, books, scientific journals, and encyclopedias. This research uses descriptive analysis, philosophical and pedagogical approaches. The results of the analysis of this study are that there are differences in legal aspects seen from the actors, regulations, mechanisms, ways of solving problems, etc. in banks and factoring institutions.